The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/aos.14638
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miR‐126 rs4636297 and miR‐146a rs2910164 polymorphisms in the susceptibility for diabetic retinopathy: a case–control study in a type 1 diabetes population

Abstract: Background and purpose MicroRNAs (miRNAs) are small non‐coding RNAs that regulate gene expression. MiRNA‐126 and miRNA‐146a have been described as having abnormal expressions in diabetic retinopathy (DR) patients. Polymorphisms in genes codifying miRNAs (miRSNPs) may alter the expression of the corresponding miRNA and, thus, interfere with susceptibility to DR. Therefore, miRSNPs in miR‐126 and miR‐146a genes could be associated with DR susceptibility. The purpose of this study was to investigate the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Results indicated there was a significant difference in the genotype distribution between patients with aged over 20 and patients aged less than 40 years old (Table 11). Results indicated that there was a significant differences in the rs3730089 SNP genotype (GG, GA, AA) between cases (09, 49, 42) and controls (18,69,35) with a p-value = 0.03 (Table 12). The A allele was associated with T2D with OR (95% CI) = 1.49 (1.01-2.21), RR = 1.19 (1.01-1.41), p-value = 0.04 (Table 13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated there was a significant difference in the genotype distribution between patients with aged over 20 and patients aged less than 40 years old (Table 11). Results indicated that there was a significant differences in the rs3730089 SNP genotype (GG, GA, AA) between cases (09, 49, 42) and controls (18,69,35) with a p-value = 0.03 (Table 12). The A allele was associated with T2D with OR (95% CI) = 1.49 (1.01-2.21), RR = 1.19 (1.01-1.41), p-value = 0.04 (Table 13).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, reduced plasma miR-126 has been suggested as a biomarker for T2DM [ 17 ]. In addition, the miR-126 rs4636297 SNP was associated with DR in T1DM patients from Brazil [ 18 ]. PI3K is a heterodimeric enzyme composed of a catalytic subunit (p110) and a regulatory subunit (p85) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms in miRNAs were associated with late complications. An rs2910164 polymorphism in seed sequence within miR-146a, leading to a reduction in mature miR-146a, was associated with diabetic nephropathy, and retinopathy [89,96]. In the southern Brazilian population, an association between the A allele of miR-126 rs4636297 and protection against diabetic retinopathy was observed [96].…”
Section: Mirnas and Late Complicationsmentioning
confidence: 99%
“…An rs2910164 polymorphism in seed sequence within miR-146a, leading to a reduction in mature miR-146a, was associated with diabetic nephropathy, and retinopathy [89,96]. In the southern Brazilian population, an association between the A allele of miR-126 rs4636297 and protection against diabetic retinopathy was observed [96]. miR-449b rs10061133 polymorphism was significantly associated with a decrease in risk for proliferative diabetic retinopathy, with a minor G allele being protective against diabetic retinopathy by altering a Dicer cleavage site [97].…”
Section: Mirnas and Late Complicationsmentioning
confidence: 99%
“…The rs4636297 (A>G) SNP is situated in the flanking region of the MIR126 gene within an intronic part of the epidermal growth factor-like protein 7 (EGFL7) gene and has been connected to post-transcriptional alterations in circulating miR-126 levels [ 28 ]. The miR-126 is an endothelial-specific miRNA and is reported as linked to endothelial activation and damage [ 29 ].…”
Section: Introductionmentioning
confidence: 99%